Management strategies for CAR-T cell therapy-related toxicities: results from a survey in Greece - Gavriilaki, Eleni; Tzannou, Ifigeneia; Vardi, Anna; Tsonis, Ioannis; Liga, Maria; Gkirkas, Konstantinos; Ximeri, Maria; Bousiou, Zoi; Bouzani, Maria; Sagiadinou, Eleftheria; Dolgyras, Panagiotis; Kotsiou, Nikolaos; et al. (Frontiers in Medicine, 2025)
Chimeric antigen receptor T-cell (CAR-T) therapy has transformed the management of relapsed or refractory hematologic malignancies, offering remarkable remission rates. However, severe toxicities, including cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS), are posing challenges to patient care. This multicenter observational study evaluated the prophylactic and treatment strategies for managing severe CRS and ICANS across six transplant centers in Greece. Data from 173 adult patients receiving CAR-T cell products—axi-cel, tisa-cel, and brexu-cel—were analyzed. The incidence of grade 3 CRS was 6.6% for axi-cel, 3.3% for tisa-cel, and 10% for brexu-cel recipients. Grade 4 CRS was documented in 2.5% and 5% in axi-cel and brexu-cel recipients, while grade 5 CRS was recorder only in brexu-cel (10%). Severe ICANS was less frequent, with grade 3 and 4 rates of 7.5% and 2.5% for axi-cel, while brexu-cel documented only grade 3 (10%). Centers utilized prophylactic measures, including levetiracetam and low-dose dexamethasone, significantly reducing severe toxicities. Tocilizumab was administered for CRS management, supplemented by anakinra or siltuximab in select cases. Early intervention strategies effectively minimized progression to severe toxicity. Our findings underscore the importance of standardized prophylactic and therapeutic protocols in mitigating CAR-T-related toxicities. The variability in toxicity incidence reflects differences in patient populations, CAR-T constructs, and clinical practices. Further research is essential to optimize individualized management strategies and advance the safety of CAR-T therapies in clinical settings.